How Oncologists Perceive the Availability and Quality of Information Generated From Patient-Reported Outcomes (PROs). (April 2020) - Shea, Michael; Audibert, Céline; Stewart, Mark; Gentile, Brittany; Merino, Diana; Hong, Agnes; Lassiter, Laura; Caze, Alexis; Leff, Jonathan; Allen, Jeff; Sigal, Ellen
Background: Despite increased incorporation of patient-reported outcome (PRO) measures into clinical trials, information generated from PROs remains largely absent from drug labeling and electronic health records, giving rise to concerns that such information is not adequately informing clinical practice. Objective: To evaluate oncologists' perceptions concerning the availability and quality of information generated from PRO measures. Additionally, to identify whether an association exists between perceptions of availability and attitudes concerning quality. Method: An online, 11-item questionnaire was developed to capture clinician perspectives on the availability and use of PRO data to inform practice. The survey also asked respondents to rate information on the basis of 4 quality metrics: "usefulness, " "interpretability, " "accessibility, " and "scientific rigor." Results: Responses were received from 298 of 1301 invitations sent (22.9% response rate). Perceptions regarding the availability of PRO information differed widely among respondents and did not appear to be linked to practice setting. Ratings of PRO quality were generally consistent, with average ratings for the 4 quality metrics between "satisfactory" and "good." A relationship was observed between ratings of PRO data quality and perceptions of the availability. Conclusion: Oncologists' attitudes toward the quality of information generated from PRO measures are favorable but not enthusiastic. These attitudes may improve as the availability of PRO data increases, given the association we observed between oncologists' ratings of the quality of PRO information and their perceptions of its availability.